Quantifying the instantaneous net drag force profile within elite front-crawl and backstroke swimming - Formosa, D. (University of the Sunshine Coast, 2012)
The aim of this research was to quantify the instantaneous net drag force profiles of elite front-crawl and backstroke swimmers. From these profiles the inter-stroke coordination, stroke symmetry and the influence of the breathing action on stroke kinetics was quantified. In study 1, an Assisted Towing Device developed in the Netherlands was compared to the earlier Measurement of Active Drag system. Nine intermediate club level swimmers, were tested randomly on both systems and significant differences (p =0.002) of 55 % in active drag were found, when swimming at the same maximum speed (mean 1.68 m.s-1, 1.40 - 1.87 m.s-1). These differences were attributed to variations in swimming styles when using the two measurement systems. The Measurement of Active Drag system was unable to measure the swimmer`s early catch phase and kick, due to the fixed length and depth of the systems push-off pads. This restricted hand placement then naturally generated a different swimming technique, when compared to the more natural free swimming style associated with the Assisted Towing Method protocol. The more natural, self-selected, arm stroke length, plus the ability to kick; and a data output of an instantaneous force-time profile, resulted in this method being the preferred testing protocol. Twenty-nine elite front-crawl and 19 elite backstroke swimmers (FINA point ranking 924.5 ± 69.0), were recruited to complete six studies to quantify factors that influence the magnitude of the intra-stroke fluctuations. These studies examined; breathing, gender differences, inter-stroke coordination and symmetry variations. This was achieved through an Assisted Towing Method which was designed and developed at the Australian Institute of Sport. The magnitude and location of the minimum and maximum net drag forces and arm symmetry were identified in Study 1. The mean location in the stroke phases where minimum and maximum net drag forces occurred were at 45 % (insweep phase) and 75 % (upsweep phase) of the front-crawl stroke, respectively. Most participants adopted an asymmetrical stroke. This study showed the advantages of representing data as an instantaneous net drag force profile, because it enabled identification of intra-stroke variations within and between individuals.